SIGNS OF INTERCOURSE: MATERIAL POETRY AND EROTIC IMPERATIVES (Gragoatá, 2004)
Rich implementations of expressive alterities within the domain of eroticism and sexuality occur in contemporary experimental poetries in Brazil, including poesia concreta, poema processo, criação intersemiótica or intersignos, and the catch-all name, poesia visual. The designation material poetry emphasizes the clearly pertinent physical qualities of language in this thematic domain and alludes to a noted title in related cultural studies, The Material Queer, which uses the modifier in a sense grounded in historical or dialectical materialism yet also offers the prospect of intriguing connections to non-normative lyrico-graphic texts with respect to identity consciousness. An embodied otherness of factitiousness on the semotic plane may be an apt partner for portraying or performing proscribed, unconventional, or non-mainstream practices: public affection, prostitution, group sex, inter-ethnic union, sodomy, homoeroticism, bisexuality, cross-dressing, fetishes, or other. In Brazilian lyric from 1950 to the present there are select moments that achieve such a confluence of interest, illustrating novelty in the trajectory of poetry as well as diversity or positioning in matters of sexuality.------------------------------------------------------------------------------SIGNOS DE RELAÇÃO: POESIA MATERIAL E IMPERATIVOS ERÓTICOSNo domínio do erotismo e da sexualidade ocorrem ricas implementações de alteridades expressivas em poesias brasileiras experimentais contemporâneas, incluindo poesia concreta, poema processo, criação intersemiótica ou intersignos, e o termo geral, poesia visual. A designação poesia material enfatiza as propriedades físicas da linguagem, evidentemente pertinentes, e alude a um título notável nos estudos culturais relacionados, The Material Queer, que usa o adjetivo num sentido baseado no materialismo dialético ou histórico, mas também oferece possibilidades de conexões fascinantes com textos lírico-gráficos não-normativos com respeito a consciência de identidade. Uma outredade factícia incorporada no plano semiótico pode ser um parceiro apto para fazer retrato ou performance de práticas proscritas, não-convencionais, fora do comum: afeto público, prostituição, sexo grupal, união inter-étnica, sodomia, homoerotismo, bissexualidade, travestismo, fetichismo, ou outras. Na lírica brasileira de 1950 para cá, há momentos seletos que realizam tal confluência de interesses, ilustrando novedade na trajetória da poesia assim como diversidade ou tomada de posição em questões de sexualidade.---Artigo em inglês.